On The Origins of Risk-Taking - Sandra E. Black; Paul J. Devereux; Petter Lundborg; Kaveh Majlesi (Lund University, School of Economics and Management, Department of Economics, 2015)
Risk-taking behavior is highly correlated between parents and their children; however, little is known about the extent to which these relationships are genetic or determined by environmental factors. We use data on stock market participation of Swedish adoptees and relate this to the investment behavior of both their biological and adoptive parents. We find that stock market participation of parents increases that of children by about 34% and that both pre-birth and post-birth factors are important. However, once we condition on having positive financial wealth, we find that nurture has a much stronger influence on risk-taking by children, and the evidence of a relationship between stock-holding of biological parents and their adoptive children becomes very weak. We find similar results when we study the share of financial wealth that is invested in stocks. This suggests that a substantial proportion of risk-attitudes and behavior is environmentally determined.
Keywords: G11; J01; 330; Nature-Nurture; Risk-taking; Portfolio choice; Investment behavior